Effectiveness of regular weighing, weight target setting and feedback by community midwives within routine antenatal care in preventing excessive gestational weight gain: randomised controlled trial. Issue 1 (December 2015) - Daley, Amanda; Jolly, K.; Jebb, S.; Roalfe, A.; Mackillop, L.; Lewis, A.; Clifford, S.; Kenyon, S.; MacArthur, C.; Aveyard, P.
Abstract Background Many pregnant women gain excess weight during pregnancy which increases the health risks to the mother and her baby. Interventions to prevent excess weight gain need to be given to the whole population to prevent excess weight gain. The aim of this study was to assess the effectiveness of a simple and brief intervention embedded withinroutine antenatal care to prevent excessive gestation weight gain. Methods Six hundred and ten pregnant women (between 10-14 weeks gestation), aged ≥18 years with a body mass index (BMI) ≥18.5 kg/m2, planned to receive community midwife led care or shared care at the time of recruitment are eligible to take part in the study. Women will be recruited from four maternity centres in England. Community midwives complete a short training module before delivering the intervention. In the intervention, midwives weigh women, set maximum weight limits for weight gain at each antenatal appointment and ask women to monitor their weight at home. Themaximum weight limit is adjusted by the midwife at each antenatal appointment if women have exceeded their maximum weight gain limit set at their previous appointment. The intervention will be compared with usual antenatal care. The primary outcome is the proportion of women per group who exceed the Institute of Medicine guidelines for gestational weight gain at 38 weeks of pregnancy according to their early pregnancy BMI category. Discussion The proposed trial will test a brief intervention comprising regular weighing, target setting and monitoring ofweight during pregnancy that can be delivered at scale as part of routine antenatal care. Using the professional expertise of community midwives, but without specialist training in weight management, the intervention will incur minimal additionalhealthcare costs, and if effective at reducing excess weight gain, is likely to be very cost effective. Trial registration Current controlled trialsISRCTN67427351 . Date assigned 29/10/2014.